New fathers: construction of the paternal role in men that participate actively in raising their children - Izquierdo E., Lorena (2015)
The present paper focuses on changes experienced in contemporary society, linked to an increasing conveyance of paternal role in raising children, leading to the birth of a “new father”, characterized by his active and increased participation in raising children. This dynamic has allowed the birth of relations that make paternal role and socially assumed norms more flexible and turn father into a figure that is able to create, maintain and strengthen emotional bonds with his children. The social significance of this study lies in the observation of relationships between father/child, child/father that depart from the mandates of a hegemonic masculinity; thus, redefining the construction of the paternal role based on paradigms which formerly prevented the active participation of men in raising their children. The study was constructed from a phenomenological paradigm with a sampling of 6 men from the Bío Bío Region in Chile, the results prove that fathers deeply desire to fully asume their role as parents, and clearly establish that both political and cultural factors restrict their participation, despite their efforts to be a full and active part of their children’s lives.